Corruption in the Digital Age: Challenges of Law Enforcement in Electronic Government Systems - Setiawan, Rahmat; Mustikowati, Endang (Ipso Jure, 2026)
The development of information technology has driven the transformation of governance through the implementation of the Electronic-Based Government System (ESBS) as an effort to realize a transparent, accountable, and efficient government. However, this digitalization does not necessarily eliminate corrupt practices, but rather gives rise to new, more complex, technology-based corruption patterns. This study aims to analyze the challenges of law enforcement against corruption crimes in the digital era within the ESBS system, particularly those caused by the ambiguity of norms in laws and regulations. The research method used is normative legal research with a legislative and conceptual approach, through an analysis of regulations related to ESBS, corruption crimes, and information technology law. The results show that the ESBS regulations in Presidential Regulation Number 95 of 2018 are still administrative in nature and have not been optimally integrated with the legal regime for eradicating corruption. In addition, there is a lack of clarity in the norms regarding the determination of legal accountability, system security standards, and digital evidence mechanisms, which creates legal uncertainty and multiple interpretations in law enforcement practices. Disharmony between the Corruption Crime Law and the Electronic Information and Transactions Law also weakens the effectiveness of enforcement against digital corruption. Therefore, legal reconstruction is needed through the reformulation of norms that are adaptive, integrative, and responsive to technological developments to ensure legal certainty and the effectiveness of eradicating corruption in the digital era.